DAMPAK KEMUDAHAN PENGGUNAAN, KUALITAS INFORMASI DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN ONLINE (STUDI PADA PENGGUNA SITUS JUAL BELI ONLINE BUKALAPAK PADA MAHASISWA FISIP UNIVERSITAS DIPONEGORO) - Kunti Nuron Nabila; Sari Listyorini (Universitas Diponegoro, 2016)
Development of Internet technology makes more businesses have sprung up selling online. One of the online buying and selling business is Bukalapak site. In the face of intense competition online business, Bukalapak need to influence consumers to make purchases on the site. Many factors influence consumers in making a purchase, such as the ease of use of the website, the quality of information provided by the website and the perception of risk will purchase online.This study aims to determine the effect of ease of use, quality of information and the perception of risk on online purchasing decisions on Bukalapak sites partially or simultaneously. This type of research is explanatory research. This research use questionnaires distributed to students FISIP Undip who have made purchases in bukalapak as many as 100 respondents. In the analysis used validity and reliability, the correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and a significance test (t test and F) with SPSS 20. The results of this study indicate that ease of use, quality of information and the perception of risk partially and simultaneously affect the online purchasing decisions. Variable ease of use provide greater influence on online purchasing decisions on Bukalapak.Based on the results of the study, the researchers suggested that Bukalapak companies further improve service websites such as displaying the menu structure is clear and understandable, product information must be clear and detailed, from the description of the size, material and color. Then, to minimize the risk of purchasing online, it is necessary to use the original photo products and provide appropriate goods delivery limit so that the delivery did not take long.